Domain-Specific Thesaurus as a Tool for Information Retrieval and Collection of Knowledge - Vladimir N. Boikov; Vladimir E. Zakharov; Mariya S. Karyaeva; Valery A. Sokolov (Моделирование и анализ информационных систем, 2013)
This paper reports basic approaches to constructive creation of an open resource named ”Domain-specified thesaurus of poetics”, which is one of the levels of an information-analytical system of the Russian poetry (IAS RP). The poetics is a group of disciplines focused on a comprehensive theoretical and historical study of poetry. IAS RP will be used as a tool for a wide range of studies allowing to determine the characteristic features of the analyzed works of poetry. Consequently, the thesaurus is the knowledge base from which one can borrow input data for training the system. The aim of our research requires a specific approach to formating the knowledge base. Thesaurus is a web-based resource which includes a domain-specific directory, information retrieval tools and tools for further analyzes. The study of glossary consisting of three thousand terms and a set of semantic fields is reviewed in this paper. Rdf-graph of the domain-specified thesaurus of poetics is presented, containing 9 types of objects and different kinds of relationships among them. Wiki-tecnologies are used for implementing a resource which allows to store data in Semantic Web formats.